Membantu Orang Muda Mencapai Integritas Diri : (Pendekatan Psikologi Kepribadian Abraham Maslow atas Amsal 12:1-16) - Christian Rezza (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2022)
Scripture is one of the sources of faith, in addition to the sacred Tradition and the Magisterium. God is Love revealing Himself to be known and let people know Him. The contents of the scriptures as written words as a means of communication and eternal unity between man and God. This means it is inseparable from the spiritual life of man which helps the growth of his personality, especially for young people. They are in the period of self-formation to become mature individuals. The Church has an obligation to build and teach all believers especially for young people through the scriptures. Therefore, the Church has endeavored to help all believers know and understand the scriptures through various methods and approaches. In this paper, the approach to the interpretation of scripture uses the science of personality psychology so that the wisdom of the book of Proverbs can touch the self -development of young people.